Association of the American Heart Association’s new “Life’s Essential 8” with all-cause and cardiovascular disease-specific mortality: prospective cohort study - Sun Jiahong; Li Yanzhi; Zhao Min; Yu Xiao; Zhang Cheng; Magnussen Costan G.; Xi Bo (BioMed Central Ltd, 2023)
Background The American Heart Association recently updated its construct of what constitutes cardiovascular health (CVH), called Life’s Essential 8. We examined the association of total and individual CVH metrics according to Life’s Essential 8 with all-cause and cardiovascular disease (CVD)-specific mortality later in  life.
Methods Data were from the National Health and Nutrition Examination Survey (NHANES) 2005–2018 at baseline linked to the 2019 National Death Index records. Total and individual CVH metric scores including diet, physical activity, nicotine exposure, sleep health, body mass index, blood lipids, blood glucose, and blood pressure were classified as 0–49 (low level), 50–74 (intermediate level), and 75–100 (high level) points. The total CVH metric score (the average of the 8 metrics) as a continuous variable was also used for dose–response analysis. The main outcomes included all-cause and CVD-specific mortality.
Results A total of 19,951 US adults aged 30–79 years were included in this study. Only 19.5% of adults achieved a high total CVH score, whereas 24.1% had a low score. During a median follow-up of 7.6 years, compared with adults with a low total CVH score, those with an intermediate or high total CVH score had 40% (adjusted hazard ratio [HR] 0.60, 95% confidence interval [CI] 0.51–0.71) and 58% (adjusted HR 0.42, 95% CI 0.32–0.56) reduced risk of all-cause mortality. The corresponding adjusted HRs (95%CIs) were 0.62 (0.46–0.83) and 0.36 (0.21–0.59) for CVD-specific mortality. The population-attributable fractions for high (score ≥ 75 points) vs. low or intermediate (score < 75 points) CVH scores were 33.4% for all-cause mortality and 42.9% for CVD-specific mortality. Among all 8 individual CVH metrics, physical activity, nicotine exposure, and diet accounted for a large proportion of the population-attributable risks for all-cause mortality, whereas physical activity, blood pressure, and blood glucose accounted for a large proportion of CVD-specific mortality. There were approximately linear dose–response associations of total CVH score (as a continuous variable) with all-cause and CVD-specific mortality.
Conclusions Achieving a higher CVH score according to the new Life’s Essential 8 was associated with a reduced risk of all-cause and CVD-specific mortality. Public health and healthcare efforts targeting the promotion of higher CVH scores could provide considerable benefits to reduce the mortality burden later in life.